Clinical decision support in the electronic health record: a primer for antimicrobial stewards and infection preventionists: work smarter so end users don’t work harder - Mary Rochelle Smith; Julie J. Lee; Marisa Holubar; Jorge L. Salinas; Mindy M. Sampson; Richard J. Medford; Amy Chang (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract